Effects of biological factors and seasonality on the level of polycyclic aromatic hydrocarbons in red mullet (Mullus barbatus). (March 2020) - Frapiccini, E.; Panfili, M.; Guicciardi, S.; Santojanni, A.; Marini, M.; Truzzi, C.; Annibaldi, A.
Abstract: This study evaluates the effects of biological factors of fish and seasonality on Polycyclic Aromatic Hydrocarbon (PAH) accumulation in red mullet ( Mullus barbatus ) tissue. Specimens were collected monthly with a bottom trawl net in an offshore fishing ground in the Northern and Central Adriatic Sea (Geographical Sub Area 17) throughout 2016. The edible fillets of 380 individuals were analyzed for the concentrations of individual PAH, total PAH, and low, medium and high molecular weight (MW) PAHs. PAH bioaccumulation was related to their physicochemical characteristics (MW, and logarithm of the octanol-water partition coefficient, log Kow ), some biological parameters of fish (body size, age, sex, reproductive stage and total lipid content), and catch season. The PAH bioaccumulation pattern and the effects of the different factors varied according to PAH MW. The heavier (medium and high MW) PAHs showed higher levels in winter-autumn and in pre-spawners compared with spawners and post-spawners. Our findings suggest that an important detoxification mechanism, albeit limited to the heavier PAHs, acts in the spawning and post-spawning stage. Low MW PAHs appeared to be unaffected by reproductive stage, lipid content and seasonality. Reproductive stage and seasonality seem to play an important role in the accumulation of heavier PAH, whereas total lipid content and age seem to exert a limited influence, and body size no effect at all. Graphical abstract: Image 1 Highlights: Polycyclic aromatic hydrocarbons (PAHs) in M. barbatus fillets were evaluated. PAH contamination was related to biological factors of fish and seasonality. PAH bioaccumulation pattern varied according to PAH molecular weight (MW). Reproductive stage and seasonality affect bioaccumulation of heavier PAHs. Low MW PAHs are unaffected by reproductive stage, lipid and seasonality.